Bronchopulmonary dysplasia: temporal trend from 2010 to 2019 in the Brazilian Network on Neonatal Research - Stolz, Camila; Costa-Nobre, Daniela Testoni; Sanudo, Adriana; de Lima Mota Ferreira, Daniela Marques; Alves, José Mariano Sales; dos Santos, Julia Paula; Miyoshi, Milton Harumi; de Mello Silva, Nathalia Moura; de Godoi Melo, Fernanda Pegoraro; da Silva, Regina Vieira Cavalcanti; Barcala, Dafne; Vale, Marynea Silva; et al. (BMJ, 2024)
Objective To evaluate the temporal trend of bronchopulmonary dysplasia (BPD) in preterm infants who survived to at least 36 weeks’ post-menstrual age (PMA) and BPD or death at 36 weeks’ PMA, and to analyse variables associated with both outcomes. Design Retrospective cohort with data retrieved from an ongoing national registry. Setting 19 Brazilian university public hospitals. Patients Infants born between 2010 and 2019 with 23–31 weeks and birth weight 400–1499 g. Main outcome measures Temporal trend was evaluated by Prais-Winsten model and variables associated with BPD in survivors or BPD or death were analysed by logistic regression. Results Of the 11 128 included infants, BPD in survivors occurred in 22%, being constant over time (annual per cent change (APC): −0.80%; 95% CI: −2.59%; 1.03%) and BPD or death in 45%, decreasing over time (APC: −1.05%; 95% CI: −1.67%; −0.43%). Being male, small for gestational age, presenting with respiratory distress syndrome, air leaks, needing longer duration of mechanical ventilation, presenting with treated patent ductus arteriosus and late-onset sepsis were associated with an increase in the chance of BPD. For the outcome BPD or death, maternal bleeding, multiple gestation, 5-minute Apgar <7, late-onset sepsis, necrotising enterocolitis and intraventricular haemorrhage were added to the variables reported above as increasing the chance of the outcome. Conclusion The frequency of BPD in survivors was constant and BPD or death decreased by 1.05% at each study year. These results show some improvement in perinatal care in Brazilian units which resulted in a reduction of BPD or death, but further improvements are still needed to reduce BPD in survivors.